A Study on the Effectiveness of Continuing Professional Development (CPD) among Professionals in the Built Environment - Folorunso , Segun Stephen; Udeh, Godwin Iheanacho; Adeniran, Adetayo Olaniyi (Management Analytics and Social Insights, 2024)
All occupations require lifelong learning to advance and remain committed to their fields. This guarantees the professional's upkeep and competence in doing their obligations with competence while upholding consumer protection and responsibility. With the advent of Congoing Professional Development (CPD), which bridges the gap between formal education and practice via professional socialization, foundational courses in education offer information and abilities that are swiftly becoming outdated. Concerns concerning the pertinent and significant subjects, substance, and delivery of the educational curriculum are also brought up by the introduction of CPD. Construction, project management, property agency, valuation, engineering, and architecture are all included in the built environment profession. Every Australian state and territory has a variety of professional groups and regulatory authorities to oversee and enforce licensing and compliance regarding CPD education needs. This study explores whether the objectives of mandatory CPD for professionals working in the built environment have been achieved. For this comparison analysis, three occupations are chosen: property agency, project management, and construction. The study explores the fundamental distinctions between these professions and highlights several CPD-related concerns between professional groups, regulatory authorities, and individuals in the field. The claim made in this study that the goals and purposes of the mandatory CPD have not been fully met is supported by statistical and descriptive data about CPD. Recommendations for improving the present system for the chosen built environment professions are included in the conclusion.